Functional circuits of LYL1 controlled by supraphysiological androgen in prostate cancer cells to regulate cell senescence - Mehdi Heidari Horestani; Katrin Schindler; Aria Baniahmad (Cell Communication and Signaling)
Abstract Background Prostate cancer (PCa) is a public health problem mostly reported in developed countries. The androgen receptor (AR) regulates the development and physiological function of normal prostate as well as the proliferation of cancerous prostate tissue. Treatment with supraphysiological androgen levels (SAL) is used in bipolar androgen therapy and inhibits PCa growth, suggesting SAL induces a tumor suppressive program. It was shown that SAL induces cellular senescence, in PCa cell lines, human tumor samples and in xenografted mouse tumor model. Methods Transcriptome and ChIP-seq analysis, PCa spheroids, knockdown (KD), co-immunoprecipitation, qRT-PCR, immune detection, in situ histochemistry. Results Here we show that LYL1 is upregulated by the clock gene BHLHE40 in both C4-2 and LNCaP cells and mediates SAL-induced cellular senescence. LYL1 is a transcriptional co-factor with oncogenic activity in leukemia. However, analysis of a large cohort of PCa patients shows that LYL1 expression is reduced during PCa development and reduced expression is significantly associated with reduced overall survival. SAL induces the expression of LYL1 through upregulation of BHLHE40. On the other hand, the KD of LYL1 enhances BHLHE40 expression via a negative feedback loop including p27kip1. Regulatory feedback loops were identified by rescue experiments. Functional analysis revealed that KD of BHLHE40 reduces whereas LYL1 KD enhances p27kip1 levels. The KD of p27kip1 suggests that this cell cycle inhibitor is a mediator of cellular senescence by the BHLHE40 - LYL1 regulatory loop. Interestingly, ChIP-seq data revealed recruitment of both AR and BHLHE40 to the LYL1 gene indicating that LYL1 is a novel direct target of both factors. Furthermore, RNA-seq data from C4-2 cells suggests that LYL1 and BHLHE40 encompass a large overlap of genes by SAL suggesting a co-regulatory activity controlled by androgens. In line with this, co-immunoprecipitation suggests LYL1 is in a complex with BHLHE40 and the AR. Conclusions Three novel feed-back loops and a novel AR- BHLHE40 / LYL1 -p27kip1 axis has been identified mediating cellular senescence in PCa cells. Graphical Abstract